Призрак Александра Вольфа - Газданов Гайто Иванович (1999)
Экземпляры: аб. (2000) / Инвентарный номер: 42777 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Г 13 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=Рус)6-4